2021
DOI: 10.3389/fnhum.2021.688818
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effect of Subthalamic Nucleus-Deep Brain Stimulation in Parkinson's Disease-Related Pain

Abstract: Pain from Parkinson's disease (PD) is a non-motor symptom affecting the quality of life and has prevalence of 20–80%. However, it is unclear whether subthalamic nucleus deep brain stimulation (STN–DBS), a well-established treatment for PD, is effective forPD-related pain. Thus, the objective of this meta-analysis was to investigate the efficacy of STN-DBS on PD-related pain and explore how its duration affects the efficacy of STN-DBS. A systematic search was performed using PubMed, Embase, and the Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Optogenetic activation of STN neurons decreases pain thresholds in mice 20 . Consistent with previous studies showing that deep brain stimulation (DBS) in the STN relieves pain in patients with Parkinson's disease [27][28][29][30][31][32][33] , we demonstrated that optogenetic inhibition of hyperactive STN neurons ameliorates hyperalgesia and central sensitization in parkinsonian mice 20 . The STN sends glutamatergic projections to both basal ganglia and non-basal ganglia structures 21,23 .…”
supporting
confidence: 91%
“…Optogenetic activation of STN neurons decreases pain thresholds in mice 20 . Consistent with previous studies showing that deep brain stimulation (DBS) in the STN relieves pain in patients with Parkinson's disease [27][28][29][30][31][32][33] , we demonstrated that optogenetic inhibition of hyperactive STN neurons ameliorates hyperalgesia and central sensitization in parkinsonian mice 20 . The STN sends glutamatergic projections to both basal ganglia and non-basal ganglia structures 21,23 .…”
supporting
confidence: 91%
“…Parkinson’s disease (PD) is a neurodegenerative disorder characterized by motor symptoms (tremor, rigidity, and slowness of movements) and several non-motor symptoms [ 1 , 2 , 3 , 4 ]. Depression, one of the most common non-motor symptoms, is a chronic and commonly reported neuropsychiatric disorder that occurs in 40%–50% of patients with PD [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is the first-line surgical treatment for Parkinson's disease (PD), it can effectively improve Parkinson's disease patients' motor and non-motor symptoms (1,2), reduce motor fluctuations, reduce dopaminergic drug use and adverse drug reactions, and improve patients' quality of life (3)(4)(5). In recent years, an increasing number of studies have discovered that non-motor symptoms, particularly emotional aspects such as anxiety and depression, have a significant impact on the quality of life of Parkinson's disease patients (6).…”
Section: Introductionmentioning
confidence: 99%